A DEBATE ON THE RELATIONSHIP BETWEEN THE NEW MIDDLE CLASS AS AN ACTOR OF CULTURAL ACTIVITIES AND GENTRIFICATION - (:unkn) unknown (ISTANBUL UNIV, METHODOLOGY & SOCIOLOGY RESEARCH CENTER, 2016)
In this article, it is intended to open up a discussion on influence of the new middle class, who is accepted as actor of gentrification process, on it, and the relation emerged within this context of the influence. Influence of the new middle class over gentrification and ascribing its spatial set-up and features through coffee shops form the very basis of the discussion. The relation between the new middle class and gentrification is addressed on the basis of coffee shops in Balat. The study, methodologically, covers field notes and semi-structured interviews which are based on participant observation between 2013-2015. Genuinity of the discussion, structured on both theoretical and field research basis, stems from the fact that it is addressed through coffee shops which are part of gentrification process in daily life, and the new middle class. In the light of existing findings three points revealed in the study are as it follows: the first, emphasis on nostalgia designed in different ways, preference of retro and vintage styles in coffeeshop decorations, exalting nostalgia as political economic and cultural politic discourse; the second, the difference based on principles of not-bothering and spending time with equivalents; and the last one, limitation of gentrification process within specific streets and roads, including those in which coffee shops are situated, or, in other words, the phenomenon of specific gentrification.
Keywords: Balat; gentrification; coffee shop; nostalgia; neighborhood; the new middle class; cultural activities